(untitled) (Global Journal of Human-Social Science, 2019)
Recruitment and selection have become essential tools in organizations because individuals with appropriate qualifications need to be attracted in sufficient numbers and on a timely basis. It is indeed surprising that despite the innovations that have been brought about by the 21st century technological transformation in the structure and practice of the recruitment and selection some countries are still caged with their moribund practice of traditional system of recruitment which are not only ineffective but inefficient in all ramifications. The objective of this paper therefore, is to examine the recruitment and selection process and procedures in Nigeria with special reference to institutions of higher learning. This is an opinion paper which made use of secondary data and on point assessment of information from the critical sector. The study revealed that the recruitment and selection process in Nigerian higher institutions is clouded in subjectivity and not based on objective criteria, which makes the whole activity inefficient and ineffective.